SISTEM INFORMASI MONITORING PRODUKSI DI PT. JIALE INDONESIA TEXTILE - Maulana Yuliati, Indah; Subhan Akbar, Agus; Azizah, Noor (Journal of Information System and Computer, 2023)
Production is the most important part of a manufacturing company, where in carrying out its production activities this company produces based on orders from customers (Job Orders). Monitoring is monitoring which can be explained as awareness of what one wants to know. Having a production monitoring information system is very useful and helpful in working in the production department because facilities are provided to see the progress of the work being done and when there is a PO that is pending, the data cannot automatically be entered, making it easier to work on running a production.